Gain-clamped L-band EDFA using narrow and broadband fiber Bragg gratings for gain-flattened - Tamchek, N.; Harun, S.W.; Poopalan, P.; Ahmad, H. (Penerbit Universiti Sains Malaysia, 2004)
In the wavelength division multiplexing (WDM) networks, the signal power in the link is varies with the changes in number of signals and link losses. A sudden signal added/dropped can caused the surviving signal have power transient (Desurvire, 1989; Sun et al., 1997) and when these signal is amplified by the erbium-doped fiber amplifier (EDFA), unequally signal power between channel became larger and causes an error detection at the receiver (Zhou et al., 2000). The increasing demand intended the networks provider to increasing link capacity. At maximum gain bandwidth of C and L band, a single fiber can carry 80 channels data (Scheerer et al., 1999) using gain-flattened EDFA has been reported.